Analysis of Directive Speech Acts in Learning Videos in the Indonesian MKU Playlist from the UNNES TV Channel - Zulfatun Ni’mah Sabila; Nanda Hanifa Qurotta A’yun; Isna Vardianawati; Riri Kumalasari; Asep Purwo Yudi Utomo; Iwan Hardi Saputro; Rossi Galih Kesuma (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A directive speech act is one of the types of speech acts intended by the speaker so that the speech partner takes action according to what is stated in his speech. The main problems in this study are (1) what are the directive speech acts contained in the learning videos on the Indonesian MKU playlist from the UNNES TV channel? And (2) what is the function of the directive speech act contained in the video. This study aims to determine the types of directive speech acts and their functions in learning videos on the Indonesian MKU playlist from the UNNES TV channel. This type of research includes qualitative descriptive research designed through data analysis research with qualitative methods which aims to describe and provide information about the problem under study by collecting data through documentation techniques. The results showed that there were four types of directive speech acts in the Indonesian MKU learning video, namely (1) direct speech acts with imperative mode, asking, soliciting, compulsion, request or request, asking and commanding; (2) Indirect speech acts with the mode of suggesting, asking, and requesting; (3) The literal speech act contains the same meaning and purpose of the speech; (4) Non-literal speech acts contain speech intentions that are different from the meaning or what is conveyed by the speaker to the speech partner. The directive speech act functions contained in the Indonesian MKU learning video include; (1) pleading, (2) asking, (3) suggesting, (4) ordering, and (5) inviting.